Python for matlab development extend matlab with 300,000+ modules from the python package index - Danial, Albert (Apress New York, 2022)
Python for MATLAB Development shows you how to enhance MATLAB with Python solutions to a vast array of computational problems in science, engineering, optimization, statistics, finance, and simulation.
Reprint 2024
index
Keywords: MATLAB; Python Computer program language